Determinants of job rotation among employees in Malaysia education sector - Wan Norsyafawati, W. Muhamad Radzi; Sayang Nurshahrizleen, Ramlan; Intan Maizura, Abd Rashid; Irza Hanie, Abu Samah; Aliana Shazma, Amir Amir; Wan Ahmad Fauzi, Wan Husain; Najuwa, Mohd Nasir (AIP Publishing, 2021)
This research explores determinants of job rotation among employees in education sector. Job rotation has become one of technique used by employers to rotate their employees’ assigned jobs throughout their employment. Most employers use job rotation as a strategy for employees to take new tasks on different jobs for a period of time before rotating back to their original position. According to Azzam (2013), job rotation is an effective administrative tool, and it is used in many organizations to achieve different goals. This research can be used for organization or employers to understand the determinants of job rotation among employees. So, a questionnaire were distributed among employees in education sector. This study are using descriptive survey to investigate the relationship between motivation, training, skill and knowledge and performance toward job rotation. Total of 342 set of questionnaire were collected out of 400 respondent. The dependent and independent variables were analysed by mean, and standard deviation and mean of frequency distribution. Statistical Package for the Social Science (SPSS) software are use in this project. Factors such as motivation, training, skill and knowledge and performance is influence the determinants of job rotation among employees in education sector were analysed. In this study, revealed that motivation, training, skill and knowledge and performance belief have significant relationship with determinants of job rotation among employees in education sector. This research could help to boosting employee’s morale. This research also recommended that future researchers should target larger sample size. REFERENCES